Pengaruh Kesehatan Mental, Motivasi Belajar, Dan Kedisiplinan Belajar Terhadap Prestasi Belajar Peserta Didik Di Madrasah Ibtidaiyah - Mei Kalimatusyaro (Pedir Research Institut, 2021)
Abstract: The low discipline of students is the concern of educators. Outside of learning, there are many students who arrive late at school, skipping school, this also happens in learning, namely there are students who are lazy to follow the teaching and learning process in class. In addition, students often leave the ongoing teaching and learning process, make noise in class, and do not do the teacher's orders in class such as doing exercises and writing notes. The two conditions above also occur in counseling activities, namely; there are students who argue that the teacher is not pleasant, students are not enthusiastic about going to school, there are students who reason that they are forced by their parents to go to school, students like to steal attention, and the presence of students disturbs their friends while studying. Some even fight when learning. This indicates a lack of motivation to learn. Based on the description above, the researcher intends to conduct research on the effect of mental health, learning motivation, and learning discipline on student achievement at Madrasah Ibtidaiyah Salafiyah Bahauddin Tamanpanjang Sidoarjo. In connection with the identification of the problems above, it is clear that the problems related to the research topic are very broad. However, due to time, energy and cost limitations, this research is focused on discussing the effects of mental health, learning motivation, and learning discipline on student achievement at Madrasah Ibtidaiyah Salafiyah Bahauddin Tamanpanjang Sidoarjo.